ISSUES OF COVERAGE OF PERFECT HUMAN SPIRITUALITY IN THE WORKS OF EASTERN THINKERS - Khalikov Qiryigit Umirzakovych; Israilov Khabibulla Abdurazokovich (Scholar Express Journals, 2023)
This article provides information about the profound ideas of Central Asian thinkers and poets Rudaki, Nasir Khisrav, Umar Khayyam, Adib Sabir Termezi, Firdavsi aimed at the formation of a perfect human spirituality
Keywords: Central Asia; Eastern thinkers; perfect man